(untitled) - Timmons, Jeffry A. (Boston, 2004)
Timmons & Spinelli's, New Venture Creation: Entrepreneurship For The 21st Century, 6/e is a perforated paperback text that covers the process of getting a new venture started, growing the venture, successfully harvesting it and starting again. Through text, case studies, and hands-on exercises, the book guides students in discovering the concepts of entrepreneurship and the competencies, skills, know-how and experience that are sufficient to pursue different entrepreneurial opportunities. The authors recognize that there is no substitute for actually starting a company, but believe that it is possible to expose students to many of the vital issues and immerse them in key learning experiences.
Keywords: New business enterprises,Entrepreneurship,Doanh nghiệp kinh doanh mới,Nhà doanh nghiệp